2003
DOI: 10.1051/agro:2003040
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of rice evapotranspiration using a microlysimeter technique and comparison with FAO Penman-Monteith and Pan evaporation methods under Moroccan conditions

Abstract: This paper reviews field measurements of evapotranspiration from paddy rice fields (ET) in an experimental station in the Gharb region of Morocco, during the summer seasons in 1995 and 1996. The results showed that the seasonal average water consumption of rice was 6.7 mm•day-1 with a maximum value of 8.3 mm•day-1 during the panicle enlargement stage (R2). The average daily ET for 1996 was compared with US Class 'A' open pan evaporation (Ep) and with reference evapotranspiration (ET 0) calculated using a valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 20 publications
2
22
0
4
Order By: Relevance
“…Measurements during flooded conditions were approximately 3.80 mm d of H 2 O lost to the atmosphere. These findings suggest that, in some cases, water status and climate have the potential to impact water use more than growth stage, similar to findings reported by others (Lage et al, 2003;Li and Cui, 1996).…”
Section: Measured Fluxessupporting
confidence: 90%
“…Measurements during flooded conditions were approximately 3.80 mm d of H 2 O lost to the atmosphere. These findings suggest that, in some cases, water status and climate have the potential to impact water use more than growth stage, similar to findings reported by others (Lage et al, 2003;Li and Cui, 1996).…”
Section: Measured Fluxessupporting
confidence: 90%
“…Rowshon et al [22] estimated crop evapotranspiration using Marriott tube lysimeter and observed ET value of 0.4-0.9 cm day −1 . Lage et al [37] conducted lysimeter experiment and reported daily average rice evapotranspiration rate of 0.67 cm day −1 . According to [38], typical evapotranspiration values of rice fields are 0.4 to 0.5 cm day −1 for wet season and 0.6 to 0.7 cm day −1 but can be as high as 1 to 1.1 cm day −1 in subtropical regions.…”
Section: Discussionmentioning
confidence: 99%
“…In general, weighable lysimeters are useful to measure crop ET, but often they are large and expensive to install and cannot partition E and T. Examples of large weighing lysimeters are given by [15] [17]- [21]. Smaller lysimeters, i.e., mini-and micro-lysimeters, have also been used to measure E, T and ET on smaller scales and examples are given by [22]- [31]. Hereafter, no distinction is made between mini-and micro-lysimeters and they are abbreviated as ML.…”
Section: Introductionmentioning
confidence: 99%
“…The ML's have been coupled with other instrumentation, including dual-probe heat-pulse, stem flow gauges, and time domain reflectometery to measure the amount of soil water loss through E and ET [31]- [35]. These ML's are normally installed and weighed early in the morning and then again weighed in evening hours using a portable scale and thus provide an estimate of day time values of soil E and ET.…”
Section: Introductionmentioning
confidence: 99%